Pulsatile Subcutaneous Hydrocortisone Replacement in Primary Adrenal Insufficiency - Simunkova, Katerina; Løvås, Kristian; Methlie, Paal; Jovanovic, Nevena; Bifulco, Ersilia; Bronstad, Ingeborg; Lightman, S. L.; Husebye, Eystein Sverre; Oksnes, Marianne (Hormone and Metabolic Research, 2023)
Pulsatile endogenous cortisol secretion is critical for physiological glucocorticoid gene signaling. Conventional glucocorticoid replacement therapy does not mimic endogenous cortisol pulsing in primary adrenal insufficiency. In an open-labeled, two-week, nonrandomized cross-over study of five patients with adrenal insufficiency (Addison’s disease in two, bilateral adrenalectomy in one, and congenital adrenal hyperplasia in two patients) we compared pulsatile and continuous cortisol pump treatment and conventional oral glucocorticoid therapy with respect to 24-h serum corticosteroid levels and plasma adrenocorticotropic hormone (ACTH). Pulsed pump restored ultradian rhythmicity as demonstrated by five peaks of serum (all patients) and subcutaneous tissue cortisol (four patients). Morning subcutaneous cortisol and cortisone were higher in continuous and pulsed pump treatment than in oral therapy despite nearly similar serum cortisol levels in all treatment arms. ACTH was within the physiological range during pulsed pump treatment in all patients except for slightly elevated levels in the morning hours 04:00–08:00 h. During oral therapy, ACTH was very high in patients with Addison’s disease and suppressed in patients with congenital adrenal hyperplasia. In conclusions, mimicking endogenous cortisol rhythmicity by ultradian subcutaneous infusion of cortisol is feasible. It was superior to both continuous pump and oral therapy in maintaining normal ACTH levels throughout the 24-h cycle. Our results demonstrate a low free cortisol bioavailability on thrice daily oral replacement therapy compared to both types of subcutaneous infusion.
Keywords: circadian rhythm; ultradian rhythm; free cortisol; primary adrenal failure; glucocorticoid replacement therapy